Neutron induced fission cross-section of 240Pu(n,f): first results from n_TOF (CERN) Experimental Area II - Tsinganis, A.; Stamatopoulos, A.; Colonna, N.; Vlastou, R.; Schillebeeckx, P.; Plompen, A.; Heyse, J.; Kokkoris, M.; Barbagallo, M.; Berthoumieux, E.; Calviani, M.; Chiaveri, E.; et al. (HNPS Advances in Nuclear Physics, 2019)
The accurate knowledge of neutron cross-sections of a variety of plutonium isotopes and other minor actinides, such as neptunium, americium and curium, is crucial for feasibility and performance studies of advanced nuclear systems (Generation-IV reactors, Accelerator Driven Systems). In this context, the 240Pu(n,f) cross-section was measured with the time-of-flight technique at the CERN n_TOF facility at incident neutron energies ranging from thermal to several MeV. The present measurement is the first to have been performed at n_TOF’s newly commissioned Experimental Area II (EAR-2), which is located at the end of an 18m neutron beam-line and features a neutron fluence that is 25-30 times higher with respect to the existing 185m flight-path (EAR-1), as well as stronger suppression of sample-induced backgrounds, due to the shorter times-of-flight involved. Preliminary results are presented.